The E6 Oncoproteins of High-Risk Papillomaviruses Bind to a Novel Putative GAP Protein, E6TP1, and Target It for Degradation - Gao, Qingshen (American Society for Microbiology, 1999)
The high-risk human papillomaviruses (HPVs) are associated with carcinomas of the cervix and other genital tumors. Previous studies have identified two viral oncoproteins, E6 and E7, which are expressed in the majority of HPV-associated carcinomas. The ability of high-risk HPV E6 protein to immortalize human mammary epithelial cells (MECs) has provided a single-gene model to study the mechanisms of E6-induced oncogenic transformation. In this system, the E6 protein targets the p53 tumor suppressor protein for degradation, and mutational analyses have shown that E6-induced degradation of p53 protein is required for MEC immortalization. However, the inability of most dominant-negative p53 mutants to induce efficient immortalization of MECs suggests the existence of additional targets of the HPV E6 oncoprotein. Using the yeast two-hybrid system, we have isolated a novel E6-binding protein. This polypeptide, designated E6TP1 (E6-targeted protein 1), exhibits high homology to GTPase-activating proteins for Rap, including SPA-1, tuberin, and Rap1GAP. The mRNA for E6TP1 is widely expressed in tissues and in vitro-cultured cell lines. The gene for E6TP1 localizes to chromosome 14q23.2-14q24.3 within a locus that has been shown to undergo loss of heterozygosity in malignant meningiomas. Importantly, E6TP1 is targeted for degradation by the high-risk but not the low-risk HPV E6 proteins both in vitro and in vivo. Furthermore, the immortalization-competent but not the immortalization-incompetent HPV16 E6 mutants target the E6TP1 protein for degradation. Our results identify a novel target for the E6 oncoprotein and provide a potential link between HPV E6 oncogenesis and alteration of a small G protein signaling pathway.